2012
DOI: 10.1002/ppul.22720
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reductions in biomass fuel exposure on symptoms of sleep apnea in children living in the peruvian andes: A preliminary field study

Abstract: Children exposed to traditional biomass fuel stoves had a higher frequency of symptoms related to sleep apnea, which decrease with improvements in biomass pollution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 22 publications
4
28
0
Order By: Relevance
“…All studies were of 3b evidence levels. A summary of the results observed is as follows: between highly versus less polluted environments, there were significant differences in snoring (25,26), initiating and maintaining sleep (20)(21)(22), sleep hyperhidrosis (20), difficulty breathing and apnea (21,23,27), and, for sickle cell anaemia children, mean and minimal nocturnal saturation (24). These results suggest an involvement (grade C) of environmental (not from voluptuary habits) pollution in the worsening of SDB in children.…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…All studies were of 3b evidence levels. A summary of the results observed is as follows: between highly versus less polluted environments, there were significant differences in snoring (25,26), initiating and maintaining sleep (20)(21)(22), sleep hyperhidrosis (20), difficulty breathing and apnea (21,23,27), and, for sickle cell anaemia children, mean and minimal nocturnal saturation (24). These results suggest an involvement (grade C) of environmental (not from voluptuary habits) pollution in the worsening of SDB in children.…”
Section: Resultsmentioning
confidence: 78%
“…Interestingly, two studies showed the beneficial effects of using less-polluting smoke stoves over SDB symptoms in children who were using before traditional smoke stoves (21,22 (26). Moreover, the geographical variation of SDB in children showed higher severity in the South part of the Varese Italian province, particularly in the Western zone close to the airport, matching the PM 10 and NO 2 distribution (27).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations